Analisis Yuridis Implementasi Qris Dalam Sistem Pembayaran Nasional: Perspektif Hukum Ekonomi Indonesia - Layya Iksiru Ghilma; Zaskia Madina; Endah Trisvina Rahayu Putri; Wildan Al Ghifari Azlin; Farahdinny Siswajanthy (Journal of Innovative and Creativity, 2026)
Bank Indonesia has established the Quick Response Code Indonesian Standard (QRIS), a national payment system standard based on QR codes, to integrate various digital payment instruments into the National Payment System. The purpose of this policy is to improve transaction convenience and the security of the payment system, especially for UMKM. The aim of this research is to examine how QRIS is regulated and implemented from the perspective of Indonesian economic law, as well as its legal impact on legal certainty, consumer protection, and healthy business competition. A normative juridical research method is used, employing legislation and conceptual analysis. The research results show that QRIS is a powerful economic legal tool with a strong legal basis. Additionally, it serves as a tool to reduce chaos in the payment system. However, there are still issues with personal data security, transaction security, and oversight efficiency. As a result, to ensure the national digital payment system continues to operate smoothly, regulatory strengthening and harmonization between regulators are needed.